Canine acquired pneumonia caused by Bordetella bronchiseptica - Luis Lantigua Tatem; Todd Veale; Christopher Richardson; Tracy Luckhardt (IDCases, 2023)
Here, we present the case of a 55-year-old male with HIV and persistent lymphopenia who developed a paroxysmal severe cough for over three weeks. Microbiology studies were positive for abundant colonies of Bordetella bronchiseptica. He reports that his dog was also ill with a severe cough, suggesting a possible canine-to-human transmission. This zoonosis has been increasingly recognized and possesses significant morbidity and mortality, especially in immunocompromised hosts.